Compare the Efficacy and Safety of Modified Combined Short and Long Axis Method versus Oblique Axis Method for Right Internal Jugular Vein Catheterization in Adult Patients (The MCSLOA Trial): Study Protocol of a Randomized Controlled Trial - Tang, Jia-Xi; Wang, Ling; Nian, Wei-Qi; Tang, Wan-Yan; Tang, Xi-Xi; Xiao, Jing-Yu; Liu, Hong-Liang (Frontiers in Surgery, 2022)
Background: Ultrasound-guided internal jugular vein (IJV) catheterization has become a standard procedure as it yields a higher success rate and fewer mechanical complications compared with an anatomical landmark technique. There are several common methods for ultrasound guidance IJV catheterization, such as short-axis out-of-plane, long-axis in-plane and oblique axis in-plane, but these technologies are still developing. It is important to further study the application of different ultrasound-guided IJV puncture techniques and find an effective and safe ultrasound-guided puncture technique. Methods: A China randomized, open-label, parallel, single center, positive-controlled, non-inferiority clinical trial will evaluate 190 adult patients undergoing elective surgery and need right jugular vein catheterization. Study participants randomized in a 1:1 ratio into control and experimental groups. The control group will take the oblique axis in-plane method for IJV catheterization. The experimental group will take the Modified combined short and long axis method. The primary endpoint of the trial is the rate of one-time successful guidewire insertion without posterior wall puncture (PWP). Secondary endpoints are the number of needle insertion attempts, the total success rate, the procedure time, and mechanical complications. Conclusion: This randomized controlled trial will evaluate the effectiveness and safety of Modified combined short and long axis method and oblique axis in-plane method for right IJV catheterization in adult patients.